1971
DOI: 10.1159/000136209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hexosamine Derivatives and Uronic Acid Derivatives on Glycosaminoglycane Metabolism of Fibroblast Cultures

Abstract: The influence of glucosamine, galactosamine, glucuronic acid and of some derivatives of these compounds on mucopolysaccharide metabolism and on protein metabolism of primary fibroblast monolayer cultures was studied. Glucosamine, glucosamine · HC1, glucosamine · HJ and glucosamine sulfate (in concentrations of 100 µg/ml each) caused a considerable, statistically highly significant increase of the secretion of mucopolysaccharides by the fibroblasts. N-Acetylglucosamine and N-acetylgalactosamine were effective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 3 publications
0
10
0
2
Order By: Relevance
“…Incorporation of exogenous glucosamine into newly synthesised glycosaminoglycans has been confirmed (Bassleer et al 1992). Specific stimulation of hyaluronan synthesis has also been demonstrated (Rodén 1956;Karzel and Domenjoz 1971;Setnikar et al 1991b). In contrast, one study has reported catabolic effects of glucosamine on canine chondrocyte cultures (Anderson et al 1999).…”
Section: Glucosaminementioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of exogenous glucosamine into newly synthesised glycosaminoglycans has been confirmed (Bassleer et al 1992). Specific stimulation of hyaluronan synthesis has also been demonstrated (Rodén 1956;Karzel and Domenjoz 1971;Setnikar et al 1991b). In contrast, one study has reported catabolic effects of glucosamine on canine chondrocyte cultures (Anderson et al 1999).…”
Section: Glucosaminementioning
confidence: 99%
“…The availability of glucosamine is a rate-limiting step in glycosaminoglycan synthesis (Karsel and Domenjoz 1971;Vidal y Plana et al 1978). Exogenous glucosamine stimulated synthesis of cartilage glycosaminoglycans and proteoglycans in vitro (Rodén 1956;Karzel and Domenjoz 1971;Vidal y Plana and Karzel 1980;Setnikar et al 1991a,b) in a dose responsive manner (Karzel and Domenjoz 1971;Vidal-y-Plana et al 1978;Bassleer et al 1992Bassleer et al , 1993. Proteoglycan biosynthesis is enhanced by 2 mechanisms: the availability of substrate for the macromolecules and a stimulating effect on the incorporation of other essential substrates (Rodén 1956).…”
Section: Glucosaminementioning
confidence: 99%
“…Almost 50% more of the sulfate salt is required to provide an equal amount of bioactive glucosamine as the hydrochloride salt, however [153]. N-acetylglucosamine was found to be less efficacious in cell culture than other glucosamine products [154]. In other species, glucosamine has been shown to enhance chondrocyte synthesis of GAGs and collagen, minimize synovitis, and provide symptomatic relief from osteoarthritis [118,153].…”
Section: Glucosamine and Chondroitinmentioning
confidence: 99%
“…[4 -7] Glucosamine, a mucopolysaccharide derived from chitin, provides a "building block" for the regeneration of glycosaminoglycans (GAG) and assists in rebuilding damaged cartilage, thus restoring articular function in most chronic arthritic patients. [1,8] Chondroitin sulfate is a viscous biological polymer of relatively high molecular weight, commonly derived from shark or bovine cartilage. [9,10] It has been commonly used in combination with glucosamine for joint maintenance.…”
Section: Introductionmentioning
confidence: 99%